2011
DOI: 10.1089/neu.2010.1518
|View full text |Cite
|
Sign up to set email alerts
|

Early Post-Traumatic Seizures in Moderate to Severe Pediatric Traumatic Brain Injury: Rates, Risk Factors, and Clinical Features

Abstract: We performed a retrospective, observational study at a level I pediatric trauma center of children with moderate-to-severe traumatic brain injury (TBI) from January 2002 to September 2006 to identify clinical and radiographic risk factors for early post-traumatic seizures (EPTS). Two hundred and ninety-nine children ages 0-15 years were evaluated, with 24 excluded because they died before the initial head computed tomography (CT) was obtained (n=20), or because their medical records were missing (n=4). Records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
99
2
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(123 citation statements)
references
References 22 publications
14
99
2
6
Order By: Relevance
“…Seventy-one percent of this cohort (102 patients) had moderate or severe TBI (initial GCS score of 3-12) and therefore underwent cEEG monitoring according to the protocol, whereas 25% (36 patients) had mild TBI (GCS score of [13][14][15]. In 4% the initial GCS score was not recorded in the database (Table 1).…”
Section: Comparison By Injury Severitymentioning
confidence: 99%
See 2 more Smart Citations
“…Seventy-one percent of this cohort (102 patients) had moderate or severe TBI (initial GCS score of 3-12) and therefore underwent cEEG monitoring according to the protocol, whereas 25% (36 patients) had mild TBI (GCS score of [13][14][15]. In 4% the initial GCS score was not recorded in the database (Table 1).…”
Section: Comparison By Injury Severitymentioning
confidence: 99%
“…2,6,13,15,17,19 Continuous electroencephalography (cEEG) is the only test to definitively diagnose subclinical seizures. It additionally offers a continuous record of any seizure activity that may have otherwise gone unwitnessed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,11) In patients with TBI, seizures during acute period could be a stimulus for secondary injury, causing poor outcome and high mortality rate. [9][10][11] Therefore prompt diagnosis and treatment of seizures are important for patients with TBI, especially during the acute period. Our study showed that the rate of SDH was high among NCS and 'suspicious NCS' patients, and most of seizures occurred postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Because NCS occurs with a high frequency in case of TBI, the prompt EEG monitoring should be performed for the diagnosis when NCS is suspected. 2,[9][10][11] In case of NCSs, non-coma inducing agents such as IV fosphenytoin and intermittent benzodiazepines could be used in addition to the oral AEDs such as valproate, levetiracetam, and topiramate. 6) All patients in our study…”
Section: Discussionmentioning
confidence: 99%